P PENGARUH TERAPI MUROTTAL AL-QUR’AN SURAH ARRAHMAN TERHADAP PERUBAHAN TINGKAT KECEMASAN PADA PASIEN PRE OPERASI DI RSUD DR. H. ANDI ABDURRAHMAN NOOR KABUPATEN TANAH BUMBU - Farhandika Putra; Tika Sari Dewy; Ahmad Junaidi (Journal of Nursing Invention, 2021)
Background: Anxiety is an unpleasant emotional state, involving subjective fear, bodily discomfort, and physical symptoms as well as a universal human experience, an unpleasant emotional response full of worry. Objective: This study is to determine the effect of AL-Quran murottal therapy Surah Arrahman on changes in anxiety levels in pre-operative patients. Methods: This research is a quantitative study, which uses a Quasi-Experimental research design with a pretest-postest without control research design. The sample in this study were 20 respondents. Results: This study used the Wilcoxon test, and obtained a P-value of 0.00 (<0.05) there were changes in anxiety levels in preoperative patients. Conclusion: This study is the effect of Murottal Al-Qur'an Surah Arrahman Therapy on changes in anxiety levels in preoperative patients at rsud dr. H. Andi Abdurrahman Noor Tanah Bumbu. Suggestion: This research is expected to the respondent to use murotal therapy as an alternative in reducing the anxiety experienced by the respondent. Al-Qur'an Murottal Therapy is more effective in reducing anxiety than other therapies so that it can be applied as a complementary therapy to reduce anxiety in preoperative patients.